Architects of buddhist leisure: socially disengaged buddhism in Asia’s museums, monuments, and amusement parks (2017)
IT IS A DISTINCT PLEASURE to be able to introduce the fi rst book in the new Contemporary Buddhism series from University of Hawai‛i Press. Following in the groundbreaking steps of George Tanabe’s Topics in Contemporary Buddhism, this series will continue to deliver the fi nest narratives and analyses of doctrine, institutions, personalities, ritual, gender, politics, economics, performance, and art in any cultural area of the Buddhist world today. The study of contemporary Buddhism has emerged as a vital and distinct fi eld in Buddhist studies. Primarily ethnographic and sociological to date, the fi eld is now expanding to include insights from political, material, and leisure studies. Justin McDaniel’s pioneering exploration of Buddhist leisure activity at monuments, parks, and museums, which he evocatively calls “socially disengaged Buddhism,” represents a signifi cant step in opening up new understandings of how Buddhism is actually encountered in the world— recreationally as much as ritually. This study is global and translocal in scope, yet intimate and personal in tone. In a fascinating shift from his earlier work on ritual, procedures, and pedagogy, McDaniel wants us to consider the “joys of Buddhists—the sensuous, entertaining, and beautiful aspects of Buddhist life” that can often be overlooked in attempts to get at “actual Buddhism.” This aff ective and aesthetic turn toward what he calls the “total experience of contemporary Buddhism” delineates an exciting new strand of Buddhist studies, one that fi rmly embeds Buddhist leisure within the realm of Buddhist learning and thus continues the necessary work of breaking down arbitrary distinctions between the secular and the religious.